```Fatela
Preuniversitarios
Logaritmos
Definición de Logaritmo
log a = c
b
Definición de Logaritmo
log a = c
b
base
Definición de Logaritmo
argumento
log a = c
b
base
Definición de Logaritmo
argumento
log a = c
b
base
logaritmo
Definición de Logaritmo
argumento
log a = c
b
base

logaritmo
bc = a
Triviales:
Triviales:
• logb 1 = 0

b0 = 1
Triviales:
• logb 1 = 0

b0 = 1
• logb b = 1

b1 = b
Importantes:
Importantes:
1) logc (a.b) = logc a + logc b
Importantes:
1) logc (a.b) = logc a + logc b
2) logc (a/b) = logc a - logc b
Importantes:
1) logc (a.b) = logc a + logc b
2) logc (a/b) = logc a - logc b
3) logb an = n . logb a
f(x) = logc x
f(x) = logc x
f(a) = logc a  cf(a) = a
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
a . b = cf(a) . cf(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
a . b = cf(a) . cf(b)
a . b = cf(a) + f(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
a . b = cf(a) . cf(b)
a . b = cf(a) + f(b)
logc (a.b) = f(a) + f(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
a . b = cf(a) . cf(b)
a . b = cf(a) + f(b)
logc (a.b) = f(a) + f(b)
f(x) = logc x
f(x) = logc x
f(a) = logc a  cf(a) = a
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b  cf(b) = b
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b 
cf(b)
=b
a
b

c
f(a)
c
f(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b 
cf(b)
=b
a
b

c
f(a)
c
f(b)
a/b = cf(a) – f(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b 
cf(b)
=b
a
b

c
f(a)
c
f(b)
a/b = cf(a) – f(b)
logc (a/b) = f(a) - f(b)
f(x) = logc x
f(a) = logc a  cf(a) = a
f(b) = logc b 
cf(b)
=b
a
b

c
f(a)
c
f(b)
a/b = cf(a) – f(b)
logc (a/b) = f(a) - f(b)
f(x) = logb x
f(x) = logb x
f(a) = logb a  bf(a) = a
f(x) = logb x
f(a) = logb a  bf(a) = a
[bf(a)]n = an
f(x) = logb x
f(a) = logb a  bf(a) = a
[bf(a)]n = an
bn.f(a) = an
f(x) = logb x
f(a) = logb a  bf(a) = a
[bf(a)]n = an
bn.f(a) = an
logb an = n . f(a)
f(x) = logb x
f(a) = logb a  bf(a) = a
[bf(a)]n = an
bn.f(a) = an
logb an = n . f(a)
• Fin de la presentación
```